Ductility Evaluation of Steel Structures with Reduced Beam Sections and Post-Tensioned Cables Using the Finite Element Method - Mehr, E. H.; Saba, H. R. (Engineering, Technology & Applied Science Research, 2017)
Given the importance of structure strengthening, this research introduces a particular type of steel structure in which the reduced beam section and post-tensioned cables were used for creating centralized property and preventing the formation of plastic hinges in the beam and columns. After introducing the system, ABAQUS modeling results are compared with a reliable laboratory sample to check its accuracy. Good convergence was seen which shows the modeling accuracy. The results of the model’s nonlinear static analysis revealed that the above steel structure has higher ductility when compared to conventional steel structures. Also, the results showed that with the rising of height, span length and early post-tensioned power of the cables we can increase the ductility of the structure.